Role-play as a community service strategy to improve english communication for nursing students - Yuriatson, Yuriatson; Rosmiaty, Rosmiaty; Taufiq, Anwar; Sasabone, Luana; Nurliah, Nurliah; Kaharto, Kaharto (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
Communication skills in English are an essential competency for nursing students to face the challenges of globalization and international healthcare services. However, many students still struggle to express themselves confidently in real clinical contexts. This community service program aimed to enhance the communication ability of nursing students through English training using the role-play method. The training was conducted with final-year nursing students at Politeknik Sandi Karsa and applied a participatory approach consisting of lectures, demonstrations, role play simulations, group discussions, and reflective evaluations. Various clinical scenarios were designed, such as explaining medication usage, calming anxious patients, and describing vital sign procedures. The program was implemented over two days, with the first day focusing on interactive material delivery and facilitator demonstrations, while the second day emphasized practical role-play performance with direct feedback. A total of 23 students participated actively in this activity. The results indicated a significant improvement in students’ confidence and ability to use English in professional healthcare communication. Participants expressed positive responses toward the method, highlighting that role play reduced speaking anxiety, increased motivation, and fostered readiness for real clinical interactions. The Focus Group Discussion (FGD) confirmed that this method not only improved English proficiency but also enhanced soft skills such as empathy, teamwork, and therapeutic communication. The outcomes suggest that role–play–based English training is an effective strategy to support nursing education and should be integrated regularly into the curriculum to prepare graduates for global healthcare demands